2006
DOI: 10.1103/physrevlett.96.175701
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Crystallization Kinetics in Colloidal Hard-Sphere Systems

Abstract: The crystallization kinetics of colloidal hard spheres was studied using a special Bragg spectrometer with high sensitivity. In contrast with the classical scenario we observe a two-step nucleation process: the number of crystallites increases slowly at early times, followed by a dramatic reduction at intermediate times, prior to undergoing a rapid increase at late times. We explain these results in terms of a polydispersity limited growth of crystallites, where the crystallization at early times is governed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
180
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(189 citation statements)
references
References 26 publications
9
180
0
Order By: Relevance
“…The best known example of such a system is given by colloidal models of hard spheres, whose crystallization behaviour has been studied extensively [2,8,10,13,[49][50][51][52]. For hard spheres, several observations have suggested that the presence of a metastable fluid-fluid demixing transition is not a necessary condition for a dense precursor-mediated crystallization process [14,16,[53][54][55][56][57][58]. The role of density fluctuations, and their priority over structural fluctuations are still subject to investigation, and for the moment the importance of both contributions cannot be ruled out [59].…”
Section: Two-step Nucleation and Precursorsmentioning
confidence: 99%
“…The best known example of such a system is given by colloidal models of hard spheres, whose crystallization behaviour has been studied extensively [2,8,10,13,[49][50][51][52]. For hard spheres, several observations have suggested that the presence of a metastable fluid-fluid demixing transition is not a necessary condition for a dense precursor-mediated crystallization process [14,16,[53][54][55][56][57][58]. The role of density fluctuations, and their priority over structural fluctuations are still subject to investigation, and for the moment the importance of both contributions cannot be ruled out [59].…”
Section: Two-step Nucleation and Precursorsmentioning
confidence: 99%
“…The dynamical arrest in 3D is expected to be enhanced by this geometrical frustration, because the system has to rearrange its local density optimized structure to reach longrange order 1 . The local geometrical frustration scenario is 1 It is found in 3D hard sphere systems that this geometrical frustration alone is not sufficient to reach a glassy state as it cannot sufficiently suppress crystallization [11,12,13], and additionally polydispersity is needed [14]. different in 2D.…”
Section: Influence Of Dimensionality On Frustrationmentioning
confidence: 99%
“…Using scattering techniques as well as microscopy, the crystallization process and the competing glass transition have been studied in detail during the past decade (see e.g. [12][13][14][15][16]). …”
Section: Introductionmentioning
confidence: 99%